Markers of extracellular matrix remodeling and systemic inflammation in patients with heritable thoracic aortic diseases - Seim, Bjørn Edvard; Holt, Margrethe Flesvig; Ratajska, Aleksandra; Michelsen, Annika; Ringseth, Monica Myklebust; Halvorsen, Bente Evy; Skjelland, Mona; Kvitting, John-Peder Escobar; Lundblad, Runar; Krohg-Sørensen, Kirsten; Osnes, Liv T. N.; Aukrust, Pål; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background In approximately 20% of patients with thoracic aortic aneurysms or dissections a heritable thoracic aortic disease (HTAD) is suspected. Several monogenic connective tissue diseases imply high risk of aortic disease, including both non-syndromic and syndromic forms. There are some studies assessing inflammation and extracellular matrix remodeling in patients with non-hereditary aortic disease, but such studies in patients with hereditary diseases are scarce. Aims To quantify markers of extracellular matrix (ECM) and inflammation in patients with vascular connective tissue diseases versus healthy controls. Methods Patients with Loeys-Dietz syndrome (LDS, n = 12), Marfan syndrome (MFS, n = 11), and familial thoracic aortic aneurysm 6 (FTAA6, n = 9), i.e., actin alpha 2 (ACTA2) pathogenic variants, were recruited. Exome or genome sequencing was performed for genetic diagnosis. Several markers of inflammation and ECM remodeling were measured in plasma by enzyme immunoassays. Flow cytometry of T-cell subpopulations was performed on a subgroup of patients. For comparison, blood samples were drawn from 14 healthy controls. Results (i) All groups of HTAD patients had increased levels matrix metalloproteinase-9 (MMP-9) as compared with healthy controls, also in adjusted analyses, reflecting altered ECM remodeling. (ii) LDS patients had increased levels of pentraxin 3 (PTX3), reflecting systemic inflammation. (iii) LDS patients have increased levels of soluble CD25, a marker of T-cell activation. Conclusion Our data suggest that upregulated MMP-9, a matrix degrading enzyme, is a common feature of several subgroups of HTAD. In addition, LDS patients have increased levels of PTX3 reflecting systemic and in particular vascular inflammation.